Association of between mental health and spiritual health among students in Shiraz University - Dastgheib, zahra; Gharlipour, zabihollah; Ghobadi Dashdebi, kamel; Hoseini, fatemeh; Vafaee, Reza (Advances in Nursing & Midwifery, 2015)
Abstract Background and aim: Spiritual health is one of the most important social – cultural factors that may predict mental health. The main purpose of this study was to assess association between mental health and spiritual health among students in Shiraz University. Materials and Method: A descriptive-correlational design was used for the study.The study was conducted in 2012. A total number of 474 students (237 female and 237 male) were recruited in this study using a cluster sampling method. Data were collected using Goldberg’s Mental Health Questionnaire and Pulutzyn and Ellison spiritual health questionnaires. Data were analyzed by SPSS16 software and two categories of descriptive and inferential statistical methods correlation and regression and t- tests. Findings: The results of the study indicated that there is a significant relationship between mental health and spiritual health scores in both sexes (P<001). Variable of spiritual health, can predict 70 percent mental health in female and male. T-test results showed that there is a difference between the means of spiritual health in boys and girls (p< 0/05). Discussion & Conclusion: Changings in the educational system and paying attention to mental health and spiritual health to meet the needs of students may be necessary. There is a need for further applied research for testing interventions to promote mental health and spiritual health students. Key Words: Mental health, spiritual health, Students REFERENCES Alahbakhshian M Jafarpour - Alavi M, Parvizi S Haghani H (2010). A survey on relationship between spiritual wellbeing and quality of life in multiple sclerosis patients. Zahedan Journal of Research in Medical Science. 12(29-33). Bahrami E Hosseini Vajari K (2003)[ The Relationship Between Religious Coping and Spiritual Happiness with Mental Health in Women]. Master’s thesis,Theran university. (Persian). Boivin M J Kirby A L Underwood L K Silva H (1999). Spiritual Well- being Scale. Measures of Religiosity. Birmingham. Religious Education Press. Corrigan P Mccorkle B Schell B (2003). Religion and spirituality in the lives of people with serious mental illness. Commmmunity Mental Health Journal. 39(6) 487-499. Craven R Hirnle C. (2003). Fundamental of Nnursing:Human Health and Function. Philadelphia, Lippincott & Williams & Wilkins Company. Esmaeil Riahi M Aliverdi -Nia A Bani Asadi M R. (2009) The impact of religiosity and religious orientation on the mental health of the students of University of Mazandaran. Journal of Social Science. 5(2) 51-90. Fernsler J I Klemm P Miller M A (1999). Spiritual well-being and demands of illness in people with colorectal cancer. Cancer Nursing. 22(2) 134-140. Ghamari-Givi H (2008 (Spirituality, identity and mental health in life span. Journal of Psychology and Religion, 1(4) 43.71(Persian). Moreira-Almeida (2006). Religiousness and Mental Health: a review, Center for the Study of Religious and Spiritual Problems (NEPER), São Paulo (SP), Department of Psychiatry,Universidade de São Paulo (USP). Mueller P S Plevak D J RummansT A (2001). Religious involvement, spirituality, and medicine: Implication for clinical practice. Mayo Clinic Proceeding, 76, 1225-1235. 1393 راهب ،84 هرامش ،24 هرود / 58 ناراکمه و ییافو اضر رتکد Narimani M Aghamohammadian H Rajabi S (2007)[ A comparison between the mental health of mothers of exceptional children and mothers of normal children]. Journal of Fundamentals of Mental Health. 9(33&34) 15-24.(Persian). Nelson C J Rosenfeld B Breitbart W Galietta M (2002). Spiritual, religion, and depression in the terminally ill. Psychosomatics. 43(3) 213-220. Omidvari S (2008). Spiritual health; concepts and challenges. Quranic Interdisciplinary Studies Journal of Iranian Students Quranic Organization. 1(1) 6-17. Palahang H (1996) Epidemiological Assessment of Mental Disorders in Kashan. Master’s thesis. Iran’s Institute of Psychiatry.(Persian). Rahimian-Boogar A Asghar Nejad A (2008). [The Relationship between psychological hardiness and ego-resiliency with mental health in adolescent and adult survivors of Bam earthquake. Iranian Journal of Psychiatry and Clinical Psychology.14(1) 62-70. Rajaei A. R. (2008). Religious Cognitive-Emotional Therapy(RCET). The 5th congress for psychotherapy. Beijingm China. SAED, A. & ROOSHAN, R. (2008). Spirituality and mental health. Journal of Psychology and Religion,2, 76-84. Salimi H Azad Marz-Abadi E Abedi Darza M (2010)[ Determining the mental health condition and its correlation with job burnout and life satisfaction in a military university personnel]. Journal of IRIAF Health Administration, 13(3) 10-17(Persian). Sanagoo A AliGhoodneh Z Asadi H (2008)[ The relationship between spiritual health and loneliness between the Persian and Turkmen youth]. Research Center of Gorgan University of Medical Sciences.(Persian). Shojaian R Zamani Monfared A (2002). The relation between use of prayers, mental health, and Job performance among technical workers of Tehran ammunition industries. Journal of Thought and Behavior. 8(30) 33-39.(Persian). Unterrainer K H Ladenhauf M L MoazediS et al (2010). Dimensions of religious/spiritual well- being and their relation to personality and psychological well-being. Personality and Individual Difference. 49(3) 192-197. Ya-Chu H Hui-Ying C Li-Yu C (2010). An exploration of the status of spiritual health among nursing students in Taiwan. Nurse Education Today. 30(5) 385-392